"One-piece" patient-specific reconstruction plate for double-barrel fibula-based mandibular reconstruction. Issue 8 (August 2020) - Yang, W.F.; Choi, W.S.; Zhu, W.Y.; Su, Y.X.
Abstract: Segmental mandibular defects require reconstruction. The fibula flap serves as a versatile flap in restoring mandibular contour and bony height. With the advances in computer-aided design and additive manufacturing technology, an innovative "one-piece" patient-specific reconstruction plate to facilitate double-barrel fibula flap shaping and bone securing was developed; the plate is described in this study. The "one-piece" plate is fabricated with individualized specifications and is mainly composed of three components: the long-bar reconstruction plate, a short-bar plate, and connecting bars. Our initial experiences showed that mandibular reconstructive surgery was greatly facilitated by the "one-piece" reconstruction plate for double-barrel fibula flap reconstruction and achieved satisfactory outcomes. A well-designed clinical trial is required to confirm the superiority of the "one-piece" reconstruction plate in the future. ClinicalTrials.gov registration: NCT03057223.